Competitive Advantages of Garut Coffee MSMEs Based on Knowledge Sharing - Rohimat Nurhasan; Ahmad Syarif Munawi; Riyad Sabilul Muminin; Yayang Iman Nur Ramdhan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
Small and Medium Enterprises Coffee shops need to increase their competitiveness to survive and develop. The knowledge and information disseminated can be technical, non-technical, or both. The research method used is quantitative with a verification type of research. Research the population of coffee shops in Garut Regency. The research sample was 47 coffee shops taken randomly with 50 respondents consisting of managers. Research data was collected by distributing questionnaires to coffee shop owners or managers. Research data was analyzed using PLS-SEM analysis. The research results show that knowledge sharing positively affects competitive advantage. Knowledge sharing enables organizations to: Increase innovation and creativity, Improve decision-making, Increase efficiency and productivity, Improve product and service quality, and Strengthen cooperation and collaboration.